Platelets in Inflammatory Disorders: A Pathophysiological and Clinical Perspective - Thachil, Jecko (Seminars in Thrombosis and Hemostasis, 2015)
Platelets are well recognized as a key cell component of the hemostatic system. Recently, several additional functions have been discovered for these blood cells but most importantly in the process of inflammation. Numerous research groups have demonstrated crucial roles for platelets in the pathogenesis of varied clinical conditions where inflammation is important. Alterations in both platelet number and function have been observed with these different conditions. The relevance of these findings is their therapeutic implications through simple antiplatelet therapy to more complex, as yet clinically untrialed options, like interfering with platelet–leukocyte or platelet–endothelial interaction. This review focuses on how platelets are relevant in inflammatory conditions with an impetus on the clinical aspects.
Keywords: inflammation; platelets; thrombosis